ANALISIS TINGKAT PENGETAHUAN DAN SIKAP MAHASISWA STIKES AL MA’ARIF BATURAJA TERHADAP PENCEGAHAN HIV/AIDS - Agustina, Fitriani; Handry Darussalam; Anggi Diandra Sayrua (Jurnal Medicare, 2025)
HIV/AIDS remains a critical global health threat, particularly among adolescents. Low levels of knowledge, attitudes, and preventive practices may increase transmission risks. This study aimed to analyze the level of knowledge, attitudes, and factors influencing HIV/AIDS prevention among students at STIKES Al Ma’arif Baturaja, considering their role as future healthcare professionals. A descriptive survey design was employed, with a sample of 76 students selected via proportional random sampling. Data were collected using structured questionnaires and analyzed descriptively to outline age, gender, knowledge, attitudes, and preventive practices. Most respondents were 18 years old (52.6%) and female (89.5%). The highest knowledge level was categorized as “moderate” (43.4%), while 77.6% exhibited “positive” attitudes toward prevention. A total of 72.4% actively engaged in preventive measures, such as using protective tools and avoiding risk behaviors. However, a gap between theoretical knowledge and practical implementation was observed, potentially influenced by external factors (environmental stigma, limited information access). Despite generally positive attitudes and preventive practices, suboptimal knowledge underscores the need for community-based education programs, skill-building training, and anti-stigma campaigns. Collaboration between educational institutions, health agencies, and community organizations is recommended to strengthen holistic HIV/AIDS prevention efforts.